The Computation of Opportunity Costs in Polychotomous Choice Models with Selectivity - Lee, Lung-fei (The Review of Economics and Statistics, 1995)
This article provides general formulas for the computation of opportunity costs (or forgone earnings) of unchosen alternatives in sample selection models with polychotomous choices. With observed choice probabilities and outcomes of alternatives chosen by some individuals, the opportunity costs for individuals who do not choose those alternatives can be evaluated. For the probability indexed sample selection models with legit choice probabilities, which include the polychotomous choice model of Lee (1983), the formulas are simple and reveal restrictions implicitly imposed on those models. These formulas can be useful for empirical studies.